Bibliographic Analysis to Calculate the Relevance of Publications - Madeira, Lucas da Cruz; Brandão, Michele A.; Gomes, Rodrigo Richard (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2018: Proceedings of the 24th Brazilian Symposium on Multimedia and the Web, 2018)
A large amount of information available on the Web challenges people to find the relevant ones. Here, we propose a new approach to help researchers to find the best references for given keywords. Such approach is based on the foundations of Lotka and Zipf laws. Also, we apply different information organization techniques to treat, store and index publications available in Scopus database. Our results reveal that our new approach is promising to identify relevant publications.